Effect of infrared pretreatment on low-humidity air drying of apple slices. Issue 4 (12th March 2017) - Shewale, Sandhya R.; Hebbar, H. Umesh
ABSTRACT: The dried apple is used in the preparation of weaning foods and bakery products. The current drying processes, especially hot air (HA) drying, still face the problem of longer processing time and product quality degradation. The low-humidity air (LHA) drying can be an option to retain product quality in heat-sensitive food such as apple. The present work focuses on the effect of pretreatment of apple slices with potassium metabisulfite and infrared (IR) waves on drying characteristics when subjected to LHA drying and comparing the product quality with conventional hot air and freeze drying (FD). Pretreatment with IR waves reduced the drying time by nearly 23 and 17% in LHA and HA drying, respectively. The results indicated that IR-treated and LHA-dried slices retained nearly 82–90 and 72–74% of ascorbic acid and total phenolic content, respectively and was comparable to FD slices. The drying time for LHA was nearly 37% lesser than that for HA drying. LHA-dried apple slices had better color and rehydration ratio compared to FD- and HA-dried slices.